Complex regional pain syndrome after transfemoral coronary balloon angioplasty - Rohan Pravinbhai Parikh; Pradeep Deshmukh (KARE Publishing, 2016)
Presently described is the case of a 55-year-old man who developed localized pain, allodynia, hyperpathia, and swelling over the right ankle joint following coronary balloon angioplasty, which had been performed via right femoral arterial access. Bone scan confirmed the diagnosis of complex regional pain syndrome. Various analgesics were administered, along with physiotherapist-assisted exercise. The present is the first reported case of complex regional pain syndrome presenting as remote postprocedural complication of transfemoral coronary balloon angioplasty.